Comparative Vascular Effects of Sirolimus and Everolimus on Isolated Human Saphenous Veins - Deniz Kaleli Durman; Erkan Civelek; Fatoş İlkay Alp Yildirim; Önder Teskin; Birsel Sönmez Uydeş Doğan (Life)
Drug-eluting stents, which release antiproliferative agents such as sirolimus and everolimus, were developed to reduce the risk of restenosis associated with bare-metal stents. However, despite their proven clinical efficacy, concerns remain regarding in-stent restenosis due to delayed endothelial healing and the risk of late thrombotic events. In this study, we aimed to determine the vascular effects of sirolimus and everolimus on isolated human saphenous vein (SV) samples obtained from patients undergoing coronary artery bypass surgery. SV rings were subjected to sirolimus and everolimus in acute and pretreatment conditions in vitro. Increasing concentrations of sirolimus (10−8–10−5 M), everolimus (10−8–10−5 M), and their vehicle were administered to SV rings precontracted with phenylephrine (Phe,10−6–5 × 10−6 M) to evaluate their direct vascular effects. Additionally, SV rings were incubated (16 h) either with sirolimus (10−5 M), everolimus (10−6 M), or the vehicle. Thereafter, the contractile responses to Phe (10−8–10−4 M), and the endothelium-dependent and endothelium-independent relaxant responses to acetylcholine (ACh, 10−8–10−4 M) and sodium nitroprusside (SNP,10−8–10−4 M) were determined, respectively. Our findings demonstrated that sirolimus and everolimus did not exert direct relaxant and modulatory effects on vascular function in isolated human SVs. Hence, the preservation of contractile and relaxant responses with sirolimus and everolimus may have clinical implications in the context of DES implantation.